The role of Pinus massoniana deadwood in promoting Plagiomnium acutum growth: effects of microbial communities and physicochemical properties - Bingyang Shi; Xiurong Wang; Shuoyuan Yang; Hongmei Chen; Yang Zhao; Qiao Liu; Rong Zou; Yannan Pan (Chemical and Biological Technologies in Agriculture)
Abstract Plagiomnium acutum holds significant industrial and medicinal value but lacks comprehensive research on cultivation technology. Deadwood is rich in nutrients and microbiota, provides a favorable environment for bryophyte growth. Nevertheless, the mechanisms by which deadwood influences moss growth are poorly understood. We conducted a pot experiment to investigate how the physicochemical properties and microbial communities of Pinus massoniana deadwood affect P. acutum growth. The results revealed that microbial community composition, abundance, and structure were altered by variations in the physicochemical properties of deadwood. Specifically, deadwood with high decay classes had higher bacterial richness and more complex fungal network structure. The comprehensive evaluation showed that the high decay classes of (W4 and W5) deadwood were more conducive to moss growth. The partial least squares path model indicated that total carbon, nitrogen, potassium, pH, phosphorus, cellulose, and condensed tannin in deadwood directly influenced the diversity and network structure of the microbial community, thereby regulating P. acutum growth. Notably, bacterial richness had the most significant impact on P. acutum. The richness and diversity of bacteria and fungi, the fungal network structure, and levels of total potassium and total nitrogen, positively influenced P. acutum growth. Specific microbiota, such as Bacillus, Bradyrhizobium, Mortierella, and Trechispora, may play a positive role in promoting P. acutum growth. These findings provide valuable insights into the mechanisms underlying moss growth promotion by deadwood and offer a reference for future research on the development and utilization of moss cultivation. Graphical Abstract